The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5530/pc.2016.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Growth Inhibitory Activity of Selected High Antioxidant Australian Syzygium Species Against the Food Poisoning and Tissue Necrotic Pathogen Clostridium Perfringens

Abstract: Introduction: Clostridium perfringens is a gram positive pathogen which is an etiological agent in Clostridial myonecrosis and enteritis necroticans. Unless promptly treated, C. perfringens infections may result in tissue necrosis and death. Syzygium australe (brush cherry) and Syzygium luehmannii (riberry) fruit and leaves have documented therapeutic properties as general antiseptic agents against an extensive panel of bacteria. Despite this, studies are yet to test the growth inhibitory activity of these spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Our study reported that all the extracts with LC 50 values < 1000 μg/mL had relatively high antioxidant capacities. Furthermore, previous studies 35 reported that the high antioxidant capacities of these Syzygium spp. is largely due to their high ascorbic acid contents.…”
Section: Quantification Of Toxicitymentioning
confidence: 90%
See 2 more Smart Citations
“…Our study reported that all the extracts with LC 50 values < 1000 μg/mL had relatively high antioxidant capacities. Furthermore, previous studies 35 reported that the high antioxidant capacities of these Syzygium spp. is largely due to their high ascorbic acid contents.…”
Section: Quantification Of Toxicitymentioning
confidence: 90%
“…34,35 Briefly, each individual plant extract was diluted in deionised water and tested across a decreasing concentration gradient. Discs were impregnated with 10 µL of the extract dilutions, allowed to dry and placed onto plates inoculated with B. linens or C. jeikeium.…”
Section: Minimum Inhibitory Concentration (Mic) Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Briefly, each individual plant extract was diluted in deionised water and tested across a decreasing concentration gradient. Discs were impregnated with 10 µL of the extract dilutions, allowed to dry and placed onto plates inoculated with Y. enterocolitica.…”
Section: Minimum Inhibitory Concentration (Mic) Determinationmentioning
confidence: 99%
“…[25][26][27] Briefly, 100 µL of each bacterial culture was grown in 10 mL of fresh nutrient broth until they reached a count of ~10 8 cells/mL. A volume of 100 µL of the bacterial suspension was spread onto nutrient agar plates and extracts were tested for antibacterial activity using 5 mm sterilised filter paper discs.…”
Section: Evaluation Of Antimicrobial Activitymentioning
confidence: 99%